1972
DOI: 10.1007/bf02633782
|View full text |Cite
|
Sign up to set email alerts
|

Surface active N‐acylglutamate: II. Physicochemical properties of long chain N‐acylglutamic acids and their sodium salts

Abstract: The physicochemical properties of long chain N‐acylglutamic acids (AGA) and their sodium salts (AGSn) are described. The solubility, Krafft point, pH value, critical micelle concentration, surface tension and foaming power were measured. The properties of the optically active AGA or AGSn differed from those of the corresponding racemates, especially in solubility. The monosodium salts generally had high Krafft points, but monosodium N‐oleoylglutamate had a low Krafft point. The monosodium salts hydrolyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…(Figures 2(a) and 2(b) ) are essentially similar except in the solid melting temperature at high surfactant concentration. The reason for that may lie in the different molecular packing and intermolecular interactions in the solid state (31,32). In the micellar solution or in the liquid crystalline states, surfactant molecules are comparatively far away, and therefore, there is no significant difference in the molecular interaction between surfactant molecules in both, DL-KDA and L-KDA systems.…”
Section: )mentioning
confidence: 99%
“…(Figures 2(a) and 2(b) ) are essentially similar except in the solid melting temperature at high surfactant concentration. The reason for that may lie in the different molecular packing and intermolecular interactions in the solid state (31,32). In the micellar solution or in the liquid crystalline states, surfactant molecules are comparatively far away, and therefore, there is no significant difference in the molecular interaction between surfactant molecules in both, DL-KDA and L-KDA systems.…”
Section: )mentioning
confidence: 99%
“…For CZE determination, such mobility changes significantly affect both peak assignment for qualitative analysis and peak area measurement for quantitative analysis. Takehara et al 17 reported that the critical micelle concentration (cmc) estimated by a conductivity method for C 12 (MW: 351) was 10.6 mM at 40˚C. It should be noted that the sample concentrations examined here were beyond the cmc (>3500 ppm).…”
Section: Effect Of Addition Of Organic Solvents On Separationmentioning
confidence: 65%
“…Generally, they have been prepared from fatty acid chlorides and amino acids [10][11][12][13][14][15] , where acid halides are used to introduce the hydrophobic groups. However, on the view point of availability of starting materials, it may not be easy to obtain optically active fatty acids compared to the availability of optically active alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, sodium salts of Nacyl amino acids are anionic surfactants with good biodegradability [1][2][3] , skin compatibility and antibacterial activity [4][5][6][7][8][9] and have been widely used in detergent, shampoo, cosmetic and food formulations. They are usually prepared from fatty acid chlorides and either pure amino acids or protein hydrolysates [10][11][12][13][14][15] . However, as the acid halides are used to introduce the hydrophobic groups, it may not be easy to vary the hydrophobic groups on the view point of availability.…”
Section: Introductionmentioning
confidence: 99%